Preparation and Gas-Sensitive Properties of SnO2@Bi2O3 Core-Shell Heterojunction Structure - Jin Liu; Yixin Gao; Yuanyuan Lv; Mengdi Yang; Haoru Guo; Neng Li; Danyang Bai; Anyi Wang (Nanomaterials)
The SnO2@Bi2O3 core-shell heterojunction structure was designed and synthesized via a hydrothermal method, and the structure and morphology of the synthesized samples were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). Based on the conclusions from XRD and SEM, it can be observed that as the hydrothermal temperature increases, the content of Bi2O3 coated on the surface of SnO2 spheres gradually increases, and the diameter of Bi2O3 nanoparticles also increases. At a hydrothermal temperature of 160 °C, the SnO2 spheres are fully coated with Bi2O3 nanoparticles. This paper investigated the gas-sensitive performance of the SnO2@Bi2O3 sensor towards ethanol gas. Gas sensitivity tests at the optimal operating temperature of 300 °C showed that the composite prepared at 160 °C achieved a response value of 19.7 for 100 ppm ethanol. Additionally, the composite exhibited excellent response to 100 ppm ethanol, with a response time of only 4 s, as well as good repeatability. The excellent gas-sensitive performance of the SnO2@Bi2O3 core-shell heterojunction towards ethanol gas is attributed to its p-n heterojunction material properties. Its successful preparation contributes to the realization of high-performance heterostructure ethanol gas sensors.